Trading with the Hudson's Bay Company, a case study of the Nipigon House Post, 1828-1838 - Odber, Kirsten (2012)
This thesis critically examines generalizations offered in the fur trade literature regarding the impact of the amalgamation of the Northwest Company and Hudson's Bay Company upon Aboriginal trade partners. There are essentially two schools of thought. One asserts that Aboriginal trappers had become dependent upon European technology by the time of the 1821 amalgamation, and were forced to continue the trade exchange accepting the changes imposed by the Hudson's Bay Company during the monopoly period. The second perspective holds that Aboriginal trade partners were not dependent upon European technology and were adaptable, choosing to opt out of the trade exchange, focusing instead upon subsistence hunting and trapping to satisfy finite wants and needs. The focus of this research project is to evaluate these competing ideas about the amalgamation phase of the fur trade, using the records of Nipigon House Post dating between 1828 and 1838. The fur trade is typically characterized by several predominant periods: the early fur trade, the competition phase, and finally the amalgamation phase. As each phase of the trade progressed, Aboriginal trade partners were affected in various ways. It is thought that in the post-amalgamation phase, there was a loss of Aboriginal bargaining power, and an extended time of hardship due to a widespread collapse in the viability of fur and food resources. This thesis examines how the Anishinabe community at Nipigon House Post was affected by the amalgamation. Data derived from the Journals of the Nipigon House are used to explore the Anishinabe community and their trade activities. Contrary to expectations deriving from the conventional fur trade literature that emphasize growing dependence upon the HBC, the Nipigon House data indicate adaptability to the monopoly period. This involved a limited demand for a narrow range of goods in keeping with the modest fur returns generated. Indeed many people focused heavily upon satisfying their subsistence needs, and sharply reduced their efforts at fur trapping. This contributed to a shift of the settlement system, with much more time spent along the lakeshore. These data suggest that the Lake Nipigon Anishinabe were not dependent upon European goods for survival. It can be concluded that reconsideration of generalizations about Aboriginal dependency during the monopoly phase of the fur trade is required.